Discrete Time Sliding Mode Control of Single Phase LCL Grid-Inverter - Makhamreh, Hamza; Kukrer, Osman (IEEE, 2017)
Current control method for single phase LCL grid connected inverters is presented. The controller is designed as a combination of feed-forward and sliding mode control. While feed-forward will play the main role in the steady state, the sliding mode controller will be active in case of parameters uncertainties and/or disturbances. The pulsed nature of the pulse width modulator is taken into account in calculations. Simulation using Matlab demonstrates the robustness of the controller against parameter uncertainties and disturbances, in addition to fast response performance.
IEEE International Conference on Industrial Technology (ICIT) -- MAR 22-25, 2017 -- Toronto, CANADA
Keywords: Grid connected inverter; discrete sliding mode; chattering phenomena